Independent actions by HIV-1 Tat and morphine to increase recruitment of monocyte-derived macrophages into the brain in a region-specific manner. (25th September 2022) - Leibrand, Crystal R.; Paris, Jason J.; Jones, Austin M.; Ohene-Nyako, Michael; Rademeyer, Kara M.; Nass, Sara R.; Kim, Woong-Ki; Knapp, Pamela E.; Hauser, Kurt F.; McRae, MaryPeace
Highlights: Tat and morphine increase macrophage recruitment within perivasculature of striatum. Within the striatum, Tat and morphine effects are independent effects. Morphine, but not Tat, increases macrophage recruitment in hippocampus. Recruitment in the perivascular space strongly predicts recruitment into parenchyma. Abstract: Despite advances in the treatment of human immunodeficiency virus (HIV), approximately one-half of people infected with HIV (PWH) experience neurocognitive impairment. Opioid use disorder (OUD) can exacerbate the cognitive and pathological changes seen in PWH. HIV increases inflammation and immune cell trafficking into the brain; however, less is known about how opioid use disorder affects the recruitment of immune cells. Accordingly, we examined the temporal consequences of HIV-1 Tat and/or morphine on the recruitment of endocytic cells (predominantly perivascular macrophages and microglia) in the dorsal striatum and hippocampus by infusing multi-colored, fluorescently labeled dextrans before and after exposure. To address this question, transgenic mice that conditionally expressed HIV-1 Tat (Tat+), or their control counterparts (Tat−), received three sequential intracerebroventricular (i.c.v.) infusions of Cascade Blue-, Alexa Fluor 488-, and Alexa Fluor 594-labeled dextrans, respectively infused 1 day before, 1-day after, or 13-days after morphine and/or Tat exposure. At the end of the study, the number of cells labeled with each fluorescent dextran were counted. The data demonstrated a significantly higher influx of newly-labeled cells into the perivascular space than into the parenchyma. In the striatum, Tat or morphine exposure increased the number of endocytic cells in the perivascular space, while only morphine increased the recruitment of endocytic cells into the parenchyma. In the hippocampus, morphine (but not Tat) increased the influx of dextran-labeled cells into the perivascular space, but there were too few labeled cells within the hippocampal parenchyma to analyze. Collectively, these data suggest that HIV-1 Tat and morphine act independently to increase the recruitment of endocytic cells into the brain in a region-specific manner.